Peripheral Blood Signature of Vasodilator-Responsive Pulmonary Arterial Hypertension. Issue 4 (27th January 2015) - Hemnes, Anna R.; Trammell, Aaron W.; Archer, Stephen L.; Rich, Stuart; Yu, Chang; Nian, Hui; Penner, Niki; Funke, Mitchell; Wheeler, Lisa; Robbins, Ivan M.; Austin, Eric D.; Newman, John H.; et al.
<x xml:space="preserve">Abstract</x> Background— Heterogeneity in response to treatment of pulmonary arterial hypertension (PAH) is a major challenge to improving outcome in this disease. Although vasodilator-responsive PAH (VR-PAH) accounts for a minority of cases, VR-PAH has a pronounced response to calcium channel blockers and better survival than vasodilator-nonresponsive PAH (VN-PAH). We hypothesized that VR-PAH has a different molecular cause from VN-PAH that can be detected in the peripheral blood. Methods and Results— Microarrays of cultured lymphocytes from VR-PAH and VN-PAH patients followed at Vanderbilt University were performed with quantitative polymerase chain reaction performed on peripheral blood for the 25 most different genes. We developed a decision tree to identify VR-PAH patients on the basis of the results with validation in a second VR-PAH cohort from the University of Chicago. We found broad differences in gene expression patterns on microarray analysis including cell-cell adhesion factors and cytoskeletal and rho-GTPase genes. Thirteen of 25 genes tested in whole blood were significantly different: EPDR1, DSG2, SCD5, P2RY5, MGAT5, RHOQ, UCHL1, ZNF652, RALGPS2, TPD52, MKNL1, RAPGEF2, and PIAS1. Seven decision trees were built with the use of expression levels of 2 genes as the primary genes: DSG2, a desmosomal cadherin involved in Wnt/β-catenin signaling, and RHOQ, which encodes a cytoskeletal protein involved in insulin-mediated signaling. These trees correctly identified 5 of 5 VR-PAH patients in the validation cohort. Conclusions— VR-PAH and VN-PAH can be differentiated with the use of RNA expression patterns in peripheral blood. These differences may reflect different molecular causes of the 2 PAH phenotypes. This biomarker methodology may identify PAH patients who have a favorable treatment response.